2022
DOI: 10.1038/s41598-022-08299-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of lipid storage droplet-2 suppresses endoreplication and induces JNK pathway-mediated apoptotic cell death in Drosophila salivary glands

Abstract: The lipid storage droplet-2 (LSD-2) protein of Drosophila is a homolog of mammalian perilipin 2, which is essential for promoting lipid accumulation and lipid droplet formation. The function of LSD-2 as a regulator of lipolysis has also been demonstrated. However, other LSD-2 functions remain unclear. To investigate the role of LSD-2, we performed tissue-specific depletion in the salivary glands of Drosophila using a combination of the Gal4-upstream activating sequence system and RNA interference. LSD-2 deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…ROS can activate JNK and p38 through a positive feedback loop, and thereby regulate the balance between apoptosis and autophagy vs cell competition, immunity, stem cell and tissue regeneration in many tissues and organs across species (Binh et al, 2022; Diwanji and Bergmann, 2020; Kucinski et al, 2017; Santabarbara-Ruiz et al, 2015) [reviewed also in (Herrera et al, 2021; La Marca and Richardson, 2020; Serras, 2022; Sinenko et al, 2021; Sui et al, 2014; Yue and Lopez, 2020; Zhou and Sakurai, 2022)]. Increased levels of ROS can propagate paracrine signals that are sensed by neighbouring healthy cells, which involve activation of Ask1 and subsequent phosphorylation and activation of JNK and p38 (Esteban-Collado et al, 2023; Serras, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…ROS can activate JNK and p38 through a positive feedback loop, and thereby regulate the balance between apoptosis and autophagy vs cell competition, immunity, stem cell and tissue regeneration in many tissues and organs across species (Binh et al, 2022; Diwanji and Bergmann, 2020; Kucinski et al, 2017; Santabarbara-Ruiz et al, 2015) [reviewed also in (Herrera et al, 2021; La Marca and Richardson, 2020; Serras, 2022; Sinenko et al, 2021; Sui et al, 2014; Yue and Lopez, 2020; Zhou and Sakurai, 2022)]. Increased levels of ROS can propagate paracrine signals that are sensed by neighbouring healthy cells, which involve activation of Ask1 and subsequent phosphorylation and activation of JNK and p38 (Esteban-Collado et al, 2023; Serras, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that LSD-2 is expressed in lipid droplets of secretory cells in the salivary gland and in the lumen of the tube where duct cells reside (Binh et al, 2022). Moreover, the role of LSD-2 in salivary gland development has been reported (Binh et al, 2022). Bi et al reported that Drosophila perilipin 1/LSD-1 localizes to large lipid droplets within larval fat bodies, whereas perilipin 2/LSD-2 is predominantly found on smaller lipid droplets (Bi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the location of LSD-1 in the Drosophila wing disc, which is a non-adipose tissue (Binh et al, 2019) (Men et al, 2016), and that LSD-2 in salivary glands localizes in the lumen of the tube in which the duct cells resided, and in the intracellular lipid droplets of secretory cells (Binh et al, 2022). In this study, LSD-1 in the salivary glands of wandering third-instar larvae of Drosophila was analyzed using Lsd-1-GFP flies which express LSD-1 tagged at the Cterminus with GFP by knocking in the GFP gene (Figure 1b,e).…”
Section: Localization Of Lsd-1 In the Salivary Gland Of Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the fat body of LSD-2 −/− homozygous larva contains less than 75% TAG as seen in normal flies. Pointing to additional functions not directly related to lipid storage, LSD-2 is also required for the endoreplication of cells in the larval salivary gland, with the loss of LSD-2 activity resulting in enhanced ROS generation and stimulation of JNK (c-jun amino-terminal kinase)-dependent apoptotic cell death [ 174 ]. Similarly, LSD-2 provides lipid storage in imaginal discs during metamorphosis, but also plays a distinct role in imaginal disc cell growth and differentiation.…”
Section: Lipid Droplets In Drosophila Melanogastermentioning
confidence: 99%